STRATEGI TIM SUKSES DALAM MEMBANGUN OPINI PUBLIK TERHADAP KOSTER DALAM RUANG MEDIA MASSA BALI POST PADA PILGUB BALI 2018 - Wira Wahyuda, I Gede Yoga; Noak, Piers Andreas; Mahaswari J.M, A.A Sagung Mirah (Jurnal Nawala Politika, 2021)
ABSTRACT Strategy is a design in achieving expectations within a certain period. Political campaigns are political communication processes carried out by political candidates in obtaining support and a good image from the public. In this research journal the strategy of the Koster-Ace winning team that uses the Political Marketing strategy as a propaganda tool in shaping public opinion in the community to get support in winning the election of the Governor of Bali. This research method uses a case study with a interview data collection technique and observation. The subject of the research was the KOSTER-ACE campaign winning team. The results of this study indicate that the Political campaign strategy used by the KOSTER-ACE winning team using the Political Marketing strategy as a propaganda tool in forming public opinion in Bali can be said to be very effective can get support and win the 2018 Bali governor election. Keywords: Mass media, political campaigns, political marketing, political image, public opinion